Efficacy of thermoresponsive, photocrosslinkable hydrogels derived from decellularized tendon and cartilage extracellular matrix for cartilage tissue engineering. (21st August 2017) - Rothrauff, Benjamin B.; Coluccino, Luca; Gottardi, Riccardo; Ceseracciu, Luca; Scaglione, Silvia; Goldoni, Luca; Tuan, Rocky S.
Abstract: Tissue engineering using adult mesenchymal stem cells (MSCs), a promising approach for cartilage repair, is highly dependent on the nature of the matrix scaffold. Thermoresponsive, photocrosslinkable hydrogels were fabricated by functionalizing pepsin‐soluble decellularized tendon and cartilage extracellular matrices (ECM) with methacrylate groups. Methacrylated gelatin hydrogels served as controls. When seeded with human bone marrow MSCs and cultured in chondrogenic medium, methacrylated ECM hydrogels experienced less cell‐mediated contraction, as compared against non‐methacrylated ECM hydrogels. However, methacrylation slowed or diminished chondrogenic differentiation of seeded MSCs, as determined through analyses of gene expression, biochemical composition and histology. In particular, methacrylated cartilage hydrogels supported minimal due to chondrogenesis over 42 weeks, as hydrogel disintegration beginning at day 14 presumably compromised cell–matrix interactions. As compared against methacrylated gelatin hydrogels, MSCs cultured in non‐methacrylated ECM hydrogels exhibited comparable expression of chondrogenic genes (Sox9, Aggrecan and collagen type II) but increased collagen type I expression. Non‐methacrylated cartilage hydrogels did not promote chondrogenesis to a greater extent than either non‐methacrylated or methacrylated tendon hydrogels. Whereas methacrylated gelatin hydrogels supported relatively homogeneous increases in proteoglycan and collagen type II deposition throughout the construct over 42 days, ECM hydrogels possessed greater heterogeneity of staining intensity and construct morphology. These results do not support the utility of pepsin‐solubilized cartilage and tendon hydrogels for cartilage tissue engineering over methacrylated gelatin hydrogels. Methacrylation of tendon and cartilage ECM hydrogels permits thermal‐ and light‐induced polymerization but compromises chondrogenic differentiation of seeded MSCs.